Effect of Cr addition on the γ′ strengthened CoNiCrAlMo compositionally complex alloy. Issue 3 (11th February 2023) - Pandey, Prafull; Pantawane, Mangesh V.; Baler, Nithin; Ravi, Raju; Makineni, Surendra Kumar; Chattopadhyay, Kamanio
Abstract : The present study illustrates the effect of varying Cr content in Co51- x Ni30 Al10 Mo5 Nb2 Ti2 Cr x ( x = 2, 5, and 8 at.-%) compositionally complex alloys (CCAs). STEM-EDS analysis suggests a change in Mo partitioning from equal in both the phases (γ and γ′) in CCA-2Cr to the γ phase in CCA-5Cr and CCA-8Cr alloys. This peculiar compositional partitioning with Cr content beyond 2% brings a change in γ′ precipitate morphology from cuboidal to spheroidal in CCAs. The shape change-induced reduction in strain energy rendered a decrease in γ′ coarsening rate by ∼ 1/2, i.e. from 11.5 to 4.6 nm 3 /s in the CCA-2Cr and CCA-8Cr alloys, respectively. All three alloys show an anomalous increase in 0.2% proof stress (PS) with temperature and achieve peak values at 770°C.